2018
DOI: 10.31661/jbpe.v0i0.713
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced Non-targeted Effect and Carcinogenesis; Implications in Clinical Radiotherapy

Abstract: Bystander or non-targeted effect is known to be an interesting phenomenon in radiobiology. The genetic consequences of bystander effect on non-irradiated cells have shown that this phenomenon can be considered as one of the most important factors involved in secondary cancer after exposure to ionizing radiation. Every year, millions of people around the world undergo radiotherapy in order to cure different types of cancers. The most crucial aim of radiotherapy is to improve treatment efficiency by reducing ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 83 publications
0
17
0
Order By: Relevance
“…Irradiation and 5-FU treatment target multiple cell types (Maxwell et al, 2003;Yahyapour et al, 2018). As BM hematopoietic cells are largely eliminated after irradiation and chemotherapy, we reasoned that this loss might be a key contributor to the observed vascular defects.…”
Section: Loss Of Hematopoietic Cells Phenocopies Irradiation-induced mentioning
confidence: 97%
“…Irradiation and 5-FU treatment target multiple cell types (Maxwell et al, 2003;Yahyapour et al, 2018). As BM hematopoietic cells are largely eliminated after irradiation and chemotherapy, we reasoned that this loss might be a key contributor to the observed vascular defects.…”
Section: Loss Of Hematopoietic Cells Phenocopies Irradiation-induced mentioning
confidence: 97%
“…It can also activate signal transduction pathways and early-response transcription factors [5]. The redox system plays an important role in acute radiation damage and is responsible for some radiation-induced early and late effects including inflammation, out-of-field effects, fibrosis, bystander effects, and others [69].…”
Section: Introductionmentioning
confidence: 99%
“…Results of several experiments have shown that cell metabolism and inflammatory responses following exposure to radiation play a key role in continuous free radical production and disruption of normal organ functions [6][7][8][9]. Attenuation of oxidative damage and inflammation following exposure to ionizing radiation can alleviate damage to radiosensitive organs, leading to increased survival [10,11].…”
Section: Introductionmentioning
confidence: 99%